Experience value as a function of hedonic and utilitarian dominant services. Issue 1 (11th January 2016) - Prebensen, Nina K; Rosengren, Sara
Abstract : Purpose: – The purpose of this paper is to examine the relative importance of dimensions of experience value in four different hedonic- and utilitarian-dominated services. Design/methodology/approach: – The proposed hypotheses are tested by an experimental design. Altogether, four different service experiences, taking place during a tourist weekend trip, were studied using a scenario-based approach. In total, 938 members of a nationally representative online panel in Sweden participated in the research. Findings: – Both hedonic and utilitarian value dimensions are present for the different experiences. However, the structures of the value dimensions differ between hedonic- and utilitarian-dominant services. Surprisingly, functional value and value for money influence satisfaction most for both categories of services. Research limitations/implications: – The design of the experiment allowed the authors to test different experiences within the same travel setting. The paper shows that all services include both hedonic and utilitarian elements, indicating awareness of what attracts tourists during the whole process of experiencing a journey. Findings suggest that further studies on different hedonic- and utilitarian-dominant firms within the different tourism service categories should be performed. Originality/value: – Theoretically, the paper only partly confirms the two structures of consumer service value, hedonic and utilitarian, revealed in earlier studies. The paper also reveals that functional value affects satisfaction more strongly in both hedonic- and utilitarian-dominant services. Several explanations for this are suggested. For the tourism industry to enhance experience value and tourist satisfaction, they should, therefore, focus on delivering functional value during the stay and probably more on emotional value in attracting visitors to travel. Results of the paper reveal that services are a part of a continuum between what is mostly utilitarian at the one end and mostly hedonic at the other end.